2015
DOI: 10.3386/w21298
|View full text |Cite
|
Sign up to set email alerts
|

Subsidy Design in Privately-Provided Social Insurance: Lessons from Medicare Part D

Abstract: Timmins, and numerous seminar participants. Decarolis is grateful to the Sloan Foundation (grant 2011-5-23 ECON) for financial support. We also gratefully acknowledge support from the National Science Foundation (SES-1357705) and the National Institute on Aging (5P01AG005842-29). The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The design of the Marketplaces themselves, with their standardized presentation of premiums and benefits, may also raise elasticities (Schmitz & Ziebarth, 2017). 6 The Medicare Part D market also involves standardized presentations, and past research has found large elasticities (between 5 and 6, larger even than those found here) for these plans which are also sold through a centralized portal (Decarolis, Polyakova, & Ryan, 2015;Lucarelli, Prince, & Simon, 2012).…”
Section: Discussionmentioning
confidence: 65%
“…The design of the Marketplaces themselves, with their standardized presentation of premiums and benefits, may also raise elasticities (Schmitz & Ziebarth, 2017). 6 The Medicare Part D market also involves standardized presentations, and past research has found large elasticities (between 5 and 6, larger even than those found here) for these plans which are also sold through a centralized portal (Decarolis, Polyakova, & Ryan, 2015;Lucarelli, Prince, & Simon, 2012).…”
Section: Discussionmentioning
confidence: 65%
“…We are motivated by an underlying tension in the literature analyzing insurance demand in market settings. A number of studies use observed insurance choices to estimate structural models of risk preferences, and then use those structural models to inform policy by predicting demand in alternative market conditions (e.g., Cohen and Einav, 2007;Decarolis et al, 2019;. The value of these counterfactual policy evaluations hinges on whether the model predictions are accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Using administrative transactional data, Curto et al () highlight the importance of considering policy structure, provider competition, and subsidies when estimating demand elasticities in the specific case of Medicare Part C. Decarolis, Polyakova, and Ryan () investigate impacts of subsidies from the supply side for Medicare Part D, focusing on estimation of welfare effects to account for the estimated $9 billion in government costs that are distributed via returns in that program. Abaluck and Gruber () find that insureds in Medicare Part D exhibit inconsistent behavior by placing more weight on plan premiums than expected out‐of‐pocket costs (realizations of which are also impacted by deductible) when valuing plan financial incentives.…”
Section: Introductionmentioning
confidence: 99%